Growth and molecular responses to long‐distance stimuli in poplars: bending vs flame wounding. Issue 2 (12th October 2013) - Tixier, Aude; Badel, Eric; Franchel, Jerome; Lakhal, Wassim; Leblanc‐Fournier, Nathalie; Moulia, Bruno; Julien, Jean‐Louis
<x xml:space="preserve">Abstract</x> Inter‐organ communication is essential for plants to coordinate development and acclimate to mechanical environmental fluctuations. The aim of this study was to investigate long‐distance signaling in trees. We compared on young poplars the short‐term effects of local flame wounding and of local stem bending for two distal responses: (1) stem primary growth and (2) the expression of mechanoresponsive genes in stem apices. We developed a non‐contact measurement method based on the analysis of apex images in order to measure the primary growth of poplars. The results showed a phased stem elongation with alternating nocturnal circumnutation phases and diurnal growth arrest phases in Populus tremula × alba clone INRA 717‐1B4. We applied real‐time polymerase chain reaction (RT‐PCR) amplifications in order to evaluate the PtaZFP2, PtaTCH2, PtaTCH4, PtaACS6 and PtaJAZ5 expressions. The flame wounding inhibited primary growth and triggered remote molecular responses. Flame wounding induced significant changes in stem elongation phases, coupled with inhibition of circumnutation. However, the circadian rhythm of phases remained unaltered and the treated plants were always phased with control plants during the days following the stress. For bent plants, the stimulated region of the stem showed an increased PtaJAZ5 expression, suggesting the jasmonates may be involved in local responses to bending. No significant remote responses to bending were observed.